Adsorption of Heavy Metals from Aqueous Solutions on Synthetic Zeolite - M. A. Barakat (The Minerals, Metals and Materials Society, 2008)
"Adsorption of heavy metal ions specifically, Cu(II), Zn(II), Mn(II), and Cr(VI) from aqueous solution on synthetic 4A Zeolite was evaluated. The 4A zeolite was synthesized previously by dehydroxylation of low grade Kalabsha Kaolin at 800 °C, and reacted hydrothermally with 2-4 M NaOH solution at 100 °C for 2h. The adsorption capacity of the metal ions were found to be strongly dependent on pH and initial metal ion concentration. At the optimium conditions the adsorption capacity decreased in the order Cu(II) > Zn(II) > Mn(II) > Cr(VI) ions. Almost complete adsorption was achieved for both of Cu(II) and Zn(II) ions at pH > 6, while the adsorption capacity for both Mn(II) and Cr(VI) was 96, and 55.3 % at pH 11 and pH 3, respectively. The results also showed that the grain size of the 4A zeolite has a little effect on the adsorption capacity. The experimental data was compared with two adsorption isotherms, Langmuir and Freundlich isotheroms. The results showed a good agreement of the Langmuir plots with the experimental data.1. IntroductionSeveral industrial wastewater streams may contain heavy metals such as Cr, Cu, Pb, Zn, Co, Ni, Mn, etc. including the waste liquids generated by metal finishing or the mineral processing industries. Heavy metals are considered hazardous pollutants due to their toxicity, even at low concentration, and nonbiodegradability. Increasing level of heavy metals in natural water bodies poses a serious threat to all living species including humans. It is, therefore, essential to reduce the heavy metal concentration in effluents/wastewater before it is discharged into the water bodies [1]."